La partición extrajudicial en la libre disposición de los bienes y la limitación del inventario vulnera derechos de igualdad y no discriminación de los legitimarios a la herencia. - Chamba Muñoz., Julio Andrés (2024)
The present work of curricular integration, entitled "The extrajudicial partition in the free disposal of assets and the limitation of the inventory violates the rights of equality and non-discrimination of the heirs to the inheritance", aims to clarify and guarantee the protection of the rights of the heirs to the inheritance. Currently, there is a great controversy regarding what article 1345 of the Civil Code and article 18 numeral 37 of the Notarial Law say, and on which this research will focus, where it is stated "... If all the co-assignees have the free disposal of their assets and attend the act, they may make the partition themselves...". The problem arises when excluding the realization of the inventory of the assets of the deceased person, greatly simplifying the procedure and violating multiple rights, such as equality and non-discrimination, the right to inheritance, due process, legal certainty, effective judicial protection, of presumed and unknown heirs. One of the ways to acquire ownership of things is succession, and therefore those who benefit from it should demonstrate to the judge not only the quality of heir, but also that there are no more than the inventoried assets, whether active or passive. Likewise, that there are no third parties to inherit such assets. This approach is very important to guarantee the legal certainty of the heirs and legatees in the extrajudicial partition process of hereditary assets. Currently, we see how this procedure has left the judicial sphere, becoming a purely administrative procedure before the Notaries of the country, based on the agreement of the parties. In this case of heirs, which is true that there is a requirement of a declaration of heirs before a competent authority, nothing is said regarding the heirs, presumed and unknown of the deceased, since the rights of these people are being violated, in addition to Due Process, who have to file lawsuits and appeals in order to have their rights restored as such.